Baryons in the relativistic jets of the stellar-mass black-hole candidate 4U 1630-47 - Trigo, M.; Miller-Jones, James; Migliari, S.; Broderick, J.; Tzioumis, T. (Nature Publishing Group, 2013)
Accreting black holes are known to power relativistic jets, both in stellar-mass binary systems and at the centres of galaxies. The power carried away by the jets, and, hence, the feedback they provide to their surroundings, depends strongly on their composition. Jets containing a baryonic component should carry significantly more energy than electron–positron jets. Energetic considerations1, 2 and circular-polarization measurements3 have provided conflicting circumstantial evidence for the presence or absence of baryons in jets, and the only system in which they have been unequivocally detected is the peculiar X-ray binary SS 433 (refs 4, 5). Here we report the detection of Doppler-shifted X-ray emission lines from a more typical black-hole candidate X-ray binary, 4U 1630-47, coincident with the reappearance of radio emission from the jets of the source. We argue that these lines arise from baryonic matter in a jet travelling at approximately two-thirds the speed of light, thereby establishing the presence of baryons in the jet. Such baryonic jets are more likely to be powered by the accretion disk6 than by the spin of the black hole7, and if the baryons can be accelerated to relativistic speeds, the jets should be strong sources of γ-rays and neutrino emission.